Efficacy and safety of an oral device to reduce food intake and promote weight loss. (11th December 2017) - Ryan, D. H.; Parkin, C. G.; Longley, W.; Dixon, J.; Apovian, C.; Bode, B.
Summary: Objective: Minimal risk weight loss tools are needed. This study's objective was to confirm Food and Drug Administration submissions of the SmartByte ™ System's safety and efficacy. Methods: This 16‐week, prospective, single‐arm, four‐centre, observational study assessed the oral device in combination with a video‐delivered lifestyle programme in adults aged 18–49 years with body mass index 27 to <35 kg m −2 . Results: Seventy‐six subjects received the device and video lifestyle instruction. The prespecified per protocol (PP) population ( N  = 40) required sensor‐verified use of the device ≥7 times per week for 14 of 16 weeks, overall device usage rate of ≥33% and study completion. At week 16, 12 (30%) achieved ≥5% weight loss, 16 (40%) achieved ≥4% and 21 (52.5%) achieved ≥3%. Week 16 mean loss for the PP population was 2.93%, and among 36 participants who did not meet PP criteria, it was 1.45%. Among 76 intent‐to‐treat subjects, two subjects reported three mild to moderate device‐related adverse events, resolving spontaneously (one hard palate abrasion and two tongue lacerations). Conclusion: The System, a minimal risk tool, can help individuals achieve meaningful weight loss, when used with a lifestyle video. More frequent device use was associated with more weight loss, on average, and greater chance of achieving ≥4% or ≥5% weight loss.